2000
DOI: 10.1007/s004240000391
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of voltage-dependent facilitation of the T-type calcium current by sodium ion in isolated frog atrial cells

Abstract: Sodium ions have been reported to alter the permeation properties of L- and N-type Ca2+ channels. Here in frog atrial cardiomyocytes under whole-cell patch-clamp conditions, we have examined the effects of lowering the external Na+ concentration on the amplitude of T-type Ca2+ current, ICaT, and on the relief of its steady-state inactivation by large depolarizing prepulses, ICaT facilitation. A partial reduction in Na+ ion concentration did not significantly alter ICaT amplitude elicited at -50 mV. However, af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…The effects of pH e were most pronounced in the absence of extracellular Ca 2+ (5 mM EDTA). Under these conditions, T-type Ca 2+ channels, like HVA Ca 2+ channels, conduct large currents of monovalent cations ( Carbone and Lux, 1987 ; Talavera et al, 1998 ; Alvarez et al, 2000 ). Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of pH e were most pronounced in the absence of extracellular Ca 2+ (5 mM EDTA). Under these conditions, T-type Ca 2+ channels, like HVA Ca 2+ channels, conduct large currents of monovalent cations ( Carbone and Lux, 1987 ; Talavera et al, 1998 ; Alvarez et al, 2000 ). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Both gating and permeation mechanisms of voltage-dependent Ca 2+ channels are modulated by ionic conditions and particularly by extracellular protons and Ca 2+ ( Prod'hom et al, 1989 ; Tytgat et al, 1990 ; Shuba et al, 1991 ; Kwan and Kass, 1993 ; Chen et al, 1996 ; Polo-Parada and Korn, 1997 ; Alvarez et al, 2000 ; Delisle and Satin, 2000 ; Shah et al, 2001 ). For T-type Ca 2+ channels in particular it has been shown previously that extracellular protons shift the voltage dependence of channel activation due to neutralization of surface charges and decrease the voltage sensitivity of channel activation, which is not consistent with the surface charge hypothesis ( Tytgat et al, 1990 ; Delisle and Satin, 2000 ; Shah et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, native I Ca,T from bullfrog atrial cells and guinea-pig coronary arterial myocytes have both been reported to display VDF properties. [48][49][50] Conversely, Zhong and coworkers reported faster recovery kinetics associated with the homologous exon 26 region in the human fetal brain Ca V 3.2 channel although neither facilitation nor potentiation (>100% fractional recovery) were observed. 35 VDF has been previously attributed to the cloned human Ca V 3.3 40,41 albeit to a much lower degree (∼20%) compared to that for the Ca V 3.2(-25) variant channel described here ( Fig.…”
Section: Discussionmentioning
confidence: 98%
“…The kinetics of this regulation is similar to that in thalamocortical neurons reported here, but the potentiation requires a strong depolarizing prepulse (more than Ϫ30 mV) and is not modified by the omission of ATP. In isolated bullfrog atrial cells, strong depolarizations (Ͼ0 mV) relieve a G i -protein-mediated inhibition of T-channel activity (Alvarez et al, 1996(Alvarez et al, , 2000, inducing a short-duration facilitation. Similarly, depolarizations larger than Ϫ30 mV can relieve a tonic current inhibition mediated by tyrosine kinases in mouse spermatogenic cells (Arnoult et al, 1998).…”
Section: Facilitation Of High-voltage-activated Camentioning
confidence: 99%